Evaluation of GSMaP Precipitation Estimates Over Indonesia - Setiyoko, Agit; Osawa, Takahiro; Nuarsa, I Wayan (International Journal of Environment and Geosciences; Vol 3 No 1 (2019)DO - 10.24843/ijeg.2019.v03.i01.p04, 2019)
Generally, observation of the rainfall in Indonesia are still conventionally using rain gauge over Indonesian region. The rain gauge network are still the most reliable source over Indonesia, however this network is not as dense as in the other major continents. The aim of this research were validation and evaluate the annual rainfall periodicity and to obtain the correction factor of the GSMaP rainfall estimation data in Indonesia. Data used in this research are daily rainfall derived from GSMaP_MVK Ver.5 and in-situ data from rain gauge measurement by BMKG from March 2000 to November 2010. The validation showed that the satellite estimate gave an underestimated condition in all of three dominant rainfall characteristics region in Indonesia. The pattern of monthly rainfall time series average based on 40 stations from March 2000 – November 2010 showed quite similar than rain gauge pattern. The relationships of monthly rainfall average showed very good agreement with rain gauge data giving very high correlation (r=0.82 – 0.92) MBE and RMSE was less than 100 mm/month. The result of spectral analysis using DFT also showed a good agreement with rain gauge spectral analysis data on monthly.